Mineral, protein and nitrate contents in leaves of Pereskia aculeata subjected to nitrogen fertilization - Maria Regina de Miranda Souza (Pesquisa Agropecuária Tropical, 2016)
Considering that nitrogen is directly related to leaf protein content, the nitrogen fertilization in Pereskia aculeata plants may affect the protein content and increase its nutritional potential. This study aimed at assessing the effect of nitrogen fertilization on mineral, protein and nitrate contents, as well as the yield of P. aculeata leaves. A randomized blocks design was used, with three replications and five treatments, consisting of increasing topdressing nitrogen doses (0-400 kg ha-1), in soil with organic matter content of 4.0 dag kg-1. Three harvests were performed for leaf analysis. No significant effect was observed for mineral and protein content or leaf fresh mass yield. The mean values for mineral composition were: 3.52 dag kg-1 of N, 0.47 dag kg-1 of P, 4.65 dag kg-1 of Ca, 0.71 dag kg-1 of Mg, 0.25 dag kg-1 of S, 36.64 mg kg-1 of Zn and 174.13 mg kg-1 of Fe. The mean content for protein was 21.86 % and the leaf fresh mass yield was 0.971 kg plant-1. K levels decreased from 50 kg ha-1 of N. Nitrate increased linearly with the nitrogen fertilization, reaching a maximum value of 78.2 mg kg-1 of fresh mass, well below the health risk threshold. It was concluded that a soil with high organic matter content does not require nitrogen fertilization. However, doses up to 400 kg ha-1 of nitrogen ensure adequate leaf yield and protein and mineral contents within the desired range for the species, being a food rich in proteins, iron and calcium.